Activity in the dorsal hippocampus-mPFC circuit modulates stress-coping strategies during inescapable stress - Yoon, Sang Ho; Song, Woo Seok; Chung, Geehoon; Kim, Sang Jeong; Kim, Myoung-Hwan (Experimental & molecular medicine, 2024)
Anatomical connectivity and lesion-deficit studies have shown that the dorsal and ventral hippocampi contribute to cognitive and emotional processes, respectively. However, the role of the dorsal hippocampus (dHP) in emotional or stress-related behaviors remains unclear. Here, we showed that neuronal activity in the dHP affects stress-coping behaviors in mice via excitatory projections to the medial prefrontal cortex (mPFC). The antidepressant ketamine rapidly induced c-Fos expression in both the dorsal and ventral hippocampi. The suppression of GABAergic transmission in the dHP-induced molecular changes similar to those induced by ketamine administration, including eukaryotic elongation factor 2 (eEF2) dephosphorylation, brain-derived neurotrophic factor (BDNF) elevation, and extracellular signal-regulated kinase (ERK) phosphorylation. These synaptic and molecular changes in the dHP induced a reduction in the immobility time of the mice in the tail-suspension and forced swim tests without affecting anxiety-related behavior. Conversely, pharmacological and chemogenetic potentiation of inhibitory neurotransmission in the dHP CA1 region induced passive coping behaviors during the tests. Transneuronal tracing and electrophysiology revealed monosynaptic excitatory connections between dHP CA1 neurons and mPFC neurons. Optogenetic stimulation of dHP CA1 neurons in freely behaving mice produced c-Fos induction and spike firing in the mPFC neurons. Chemogenetic activation of the dHP-recipient mPFC neurons reversed the passive coping behaviors induced by suppression of dHP CA1 neuronal activity. Collectively, these results indicate that neuronal activity in the dHP modulates stress-coping strategies to inescapable stress and contributes to the antidepressant effects of ketamine via the dHP-mPFC circuit. Dorsal hippocampus neuronal activity modulates stress-coping strategies in mice Understanding our brain’s handling of emotions and thought is vital. Recent research indicates that different sections of the hippocampus are responsible for either thought processing or emotional reactions. However, new research by Yoon et al. disputes this, demonstrating that both hippocampus sections can affect behavior via connections with the prefrontal cortex, a brain area involved in decision-making. This study, a mouse experiment, examined how a specific pathway between the dorsal hippocampus and the medial prefrontal cortex impacts behavior, especially in response to stress and depression-like symptoms. The researchers used various methods, including gene alteration and behavioral tests, to understand how changes in this pathway’s activity affect behavior. This study paves the way for future research to explore how these brain areas interact in the context of emotional and thought processing, potentially leading to more effective depression treatments. This summary was initially drafted using artificial intelligence, then revised and fact-checked by the author.